Modal analysis and tilt drop-test of 1 inch seagate hard disk drive using laser doppler vibrometer - Tan, Berwyn Guanyong. (2009)
Hard disk drives are no longer confined to the desktop PC, they are utilized in many portable devices such as hand held gaming devices and laptops. Such disk drives are becoming increasingly smaller in size and are prone to being dropped and mishandled, shortening product lifespan and leading to product failure. One way to improve the resilience of hard disk drives is to study their modal properties and response to shock.